Excipients in the Paediatric Population: A Review - Khadija Rouaz; Blanca Chiclana-Rodríguez; Anna Nardi-Ricart; Marc Suñé-Pou; Dèbora Mercadé-Frutos; Josep María Suñé-Negre; Pilar Pérez-Lozano; Encarna García-Montoya (MDPI AG, 2021)
This theoretical study seeks to critically review the use of excipients in the paediatric population. This study is based on the rules and recommendations of European and American drug regulatory agencies. On the one hand, this review describes the most frequent excipients used in paediatric medicine formulations, identifying the compounds that scientific literature has marked as potentially harmful regarding the side effects generated after exposure. On the other hand, this review also highlights the importance of carrying out safety -checks on the excipients, which, in most cases, are linked to toxicity studies. An excipient in the compilation of paediatric population databases is expected to target safety and toxicity, as in the STEP database. Finally, a promising pharmaceutical form for child population, ODT (Orally Disintegrating Tablets), will be studied.